Leaching and drying of neem flakes (Azadirachta indica) to obtain a botanical insecticide (Nexo Revista Científica, 2015)
The aim of this work is to experimentally study the feasibility of improving the processing of neem flakes in columns by performing the leaching of insecticide without intermediate removal of the non-polar solvent, and by performing simultaneously both leaching steps. The drying of the solvents remaining in the neem flakes is also experimentally studied. In the leaching part, the parameters studied were leaching time, thickness of the flakes, volume ratio of solvents, and total volume of solvents. These parameters showed to have a great influence on the yield of insecticide components, but the influence of solvent ratio was the most important one. It was shown that more methanol than hexane had to be used to obtain a large yield of insecticide compounds. The yield of oil was mainly influenced of the flake thickness. In the drying part, the temperature of the incoming airflow has influence on the process. Conclusions about the drying time or the drying rate are not possible to make from the results of the experiments. The variations in drying time are too large and the drying rate seems to be independent of the conditions of the previous leaching step.